Blood pressure, inflammation, and quality of life in patients treated with different renal replacement therapies. Issue 1 (2nd January 2022) - Altun, Eda; Paydas, Saime; Kaya, Bülent; Balal, Mustafa; Seydaoğlu, Gülsah
Abstract: Our aim was to determine the relationship between the modality of renal replacement therapy and inflammation markers, BP control, and quality of life (QoL). Sixteen hemodialysis, 17 peritoneal dialysis patients, and 27 kidney transplant receivers (KTr) have been included in this study. Short Form‐36 (SF‐36) for the evaluation of QoL and ambulatory BP monitoring were performed on the same day. Erythrocyte sedimentation rate, CRP, IL‐6, and IL‐10 were measured. While the mean IL‐10, IL‐6, and CRP levels were the highest in the dialysis groups, there were no significantly differences any parameters for all groups. QoL was better in the KTr almost as in healthy controls but worse in the dialysis patients. It should be taken into account that hypertension may occur at night even if the daytime BP is normal in KTr.